PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IVA SD NEGERI 32 PEKANBARU - Marliyah '; Hamizi '; Erlisnawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research which was executed by using the application of Cooperative Learning typed Think Pair Share (TPS) in learning mathematics is aimed to handle the problem of the low learning mathematics score for the sixth grade student at Elementary School 32 Pekanbaru. This research is Class Action Research (CAR) which was executed collaboratively between researcher and homeroom teacher of the fifth a class. The research was executed in three cycles. The research data was obtained from the observations of the teacher’s activity and the student’s activity when an action was done and the result of the student’s evaluation in the end of each cycle. The result of the research refers to the enhancement of the student’s mathematics score in the fifth class of Elementary School 32 Pekanbaru after being done an action in learning by using Cooperative Model Typed Think Pair Share (TPS). This one can be seen from the score of the student’s evaluation. The result of learning before an action was categorized in low score is 62,36, where as in the evaluation of the first cycle is 80,90, the evaluation of the second cycle is 88,18. The percentage of the teacher’s activity in the first cycle is 72,92% in Good category, 91,67% in the second cycle in very good category. whereas the percentage of the student’s activity in the first cycle is 68,75% in Good category, the percentage in the second cycle is the last one is 87,5% in Very Good category. Based on the research and analyses, the conclusion is the application of Cooperative Learning model typed Think Pair Share (TPS) can increase the mathematics in the sixth grade student at Elementary School 32 Pekanbaru.Keyword : Think Pair Share, TPS, The Result Of Learning Mathematics, Cooperative Learning